Development of Smart Home System for NTU Hall Residents - Chan, Zhen Yue (2017)
Smart Home is an act of using devices and programming through a network to control basic home functions for better quality living. It reduces human interaction as much as technically possible and replacing them with programmed electronic systems. This designed smart home system aims to improve the living quality of the hall residents, it includes various features for security, entertainment and appliances surveillance. [Peer Assessment Review]